2022
DOI: 10.1029/2021ja030089
|View full text |Cite
|
Sign up to set email alerts
|

Lobe Reconnection and Cusp‐Aligned Auroral Arcs

Abstract: Following the St. Patrick's Day (17 March) geomagnetic storm of 2013, the interplanetary magnetic field had near‐zero clock angle for almost two days. Throughout this period multiple cusp‐aligned auroral arcs formed in the polar regions; we present observations of, and provide a new explanation for, this poorly understood phenomenon. The arcs were observed by auroral imagers onboard satellites of the Defense Meteorological Satellite Program. Ionospheric flow measurements and observations of energetic particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 73 publications
8
49
1
Order By: Relevance
“…Zhang et al (2016) proposed multiple TPAs to be caused by field-aligned current (FAC) filaments mapping into the polar cap that have been caused by local reconnection during Kevin-Helmholtz instabilities at the tail flanks. Milan et al (2022) suggested that temporal dual-lobe reconnection during strongly northward IMF would cause alternating strips of open and closed field lines in the polar cap, ultimately leading to a closure of the polar in form of multiple cusp-aligned TPAs.…”
Section: Based On the Observed Imfmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al (2016) proposed multiple TPAs to be caused by field-aligned current (FAC) filaments mapping into the polar cap that have been caused by local reconnection during Kevin-Helmholtz instabilities at the tail flanks. Milan et al (2022) suggested that temporal dual-lobe reconnection during strongly northward IMF would cause alternating strips of open and closed field lines in the polar cap, ultimately leading to a closure of the polar in form of multiple cusp-aligned TPAs.…”
Section: Based On the Observed Imfmentioning
confidence: 99%
“…They are typically cusp‐aligned (Zhang et al., 2016) and fill both the dawn and dusk oval sides simultaneously, resulting in a small teardrop‐shaped polar cap area devoid of aurora (in e.g., Murphree et al., 1982, Hones et al., 1989, Tanaka et al., 2017, and Milan et al., 2020 described as horse‐collar aurora). Occasionally, multiple TPAs fill the entire polar cap (for examples, see Zhang et al., 2016 their Figure 2 or Milan et al., 2022, their Figure 3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that the HCA is located on closed field lines, the polar cap became very small and teardrop-shaped 24,31,32 when the HCA formed. After about 1 hour (around 3 hours after IMF turn north), the two poleward edges of the HCA merged together around the noon-midnight meridian with sunward flows around dayside cusp region in both hemispheres indicating ongoing dual-lobe reconnections (DLRs) (blue curve in Figure 2 a and g and Supplementary Figure S1) 23,24,33 . This suggests that the polar cap nearly disappeared (normally the polar cap is empty without discrete auroral emissions and linked to the open lobe field line region) and that a nearly fully closed magnetosphere was generated by dual-lobe reconnection 16,28 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we argued that the weak tendency for the duskward movement of space hurricanes with the increasing IMF clock angle (see Figure 4C) is related to the extension of the reconnection site in the dayside magnetopause under the nonzero IMF By. Under positive/negative IMF By, the reconnection site extends toward dusk/dawn in the Northern Hemisphere (Luhmann et al, 1984;Park et al, 2006), and the open flux tubes are added asymmetrically to the magnetosphere (Cowley, 1981;Tenfjord et al, 2015;Milan et al, 2022). The evolution of polar cap aurora-like transpolar arcs is also modulated by IMF By, which is related to the night-side magnetotail process (Fear and Milan, 2012;Xing et al, 2018).…”
Section: Temporal and Spatial Distributionmentioning
confidence: 99%